2014
DOI: 10.1016/j.eururo.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation Sequencing of Advanced Prostate Cancer Treated with Androgen-deprivation Therapy

Abstract: BackgroundAndrogen-deprivation therapy (ADT) is standard treatment for locally advanced or metastatic prostate cancer (PCa). Many patients develop castration resistance (castration-resistant PCa [CRPC]) after approximately 2–3 yr, with a poor prognosis. The molecular mechanisms underlying CRPC progression are unclear.ObjectiveTo undertake quantitative tumour transcriptome profiling prior to and following ADT to identify functionally important androgen-regulated pathways or genes that may be reactivated in CRPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 37 publications
14
129
0
Order By: Relevance
“…Androgen deprivation therapy (ADT), the standard of care for patients with locally advanced disease, metastatic disease, or biochemical recurrence after definitive primary therapy, has been demonstrated to provide an initial benefit. [1][2][3] Unfortunately, castration resistance predicts a more ominous outcome with a median patient survival time of 2 years. Castration-resistant prostate cancer (CRPC), previously known as hormone-refractory prostate cancer, is now understood to be a progressive of disease despite medical or surgical castration.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT), the standard of care for patients with locally advanced disease, metastatic disease, or biochemical recurrence after definitive primary therapy, has been demonstrated to provide an initial benefit. [1][2][3] Unfortunately, castration resistance predicts a more ominous outcome with a median patient survival time of 2 years. Castration-resistant prostate cancer (CRPC), previously known as hormone-refractory prostate cancer, is now understood to be a progressive of disease despite medical or surgical castration.…”
Section: Introductionmentioning
confidence: 99%
“…These were validated to be significant (P<0.05) by statistical analysis. Another tankyrase inhibitor, XAV939, has been recently shown to inhibit proliferation in a CRPC LNCaP cell line, but have only a minor inhibition in LNCaPs themselves (5). I also observed that inhibition was more pronounced in C4-2 cells compared to LNCaPs, which is also a reflection that C4-2 cells grow at a faster rate than LNCaP cells.…”
Section: Summary Of Aimmentioning
confidence: 80%
“…Next generation sequencing of prostate cancer prior to and following androgen deprivation therapy has dramatically helped to identify important androgen-regulated pathways or genes that may be reactivated in CRPC [15]. Specifically, chromosomal rearrangements, amplifications, deletions, or point mutations and DNA methylation alterations allow for emerging aggressive clones [16].…”
Section: Chromoplexy and Chromotripsis Modelsmentioning
confidence: 99%